The role of trust and poverty in compliance with social distancing measures in Africa during the COVID-19 pandemic - Edson Mazive; Gerson Baza; Gimelgo Xirinda; Ivan Manhique; Jorge Mouco; Silvestre Matola (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Since it began, the COVID-19 pandemic has imposed a number of challenges on Africa and the rest of the world. Following the recommendations of the World Health Organization, many countries imposed social distancing measures and cancelled non-essential activities in order to contain the spread of the virus, reduce the infection rate, and ease the pressure on the health system. The literature shows that observance of these measures is based on trust in the government and the rest of society, trust in health policies, belief and trust in science, individual risk perception, and expectations regarding the duration of the restrictions. In this study, we have joined the new and growing body of literature by asking how trust in 18 African countries shapes commitment to the measures set out above. The results show that people's trust in public institutions reinforces the effect of the measures. On the other hand, poverty and trust between people weaken the measures, and the latter can even cancel out the measures' effect.
Keywords: B55; C33; E71; I32; 330; COVID-19; social distancing; trust in public institutions; Africa